FEATURES OF MEDICAL SERVICES IN UKRAINE - ZRYBNIEVA, Iryna; Gavrysh, Iryna (Natural Science Readings: abstracts book, 2021)
Services focused on human capital development are one of the most important in today's economic environment. Significant influence on the processes of economic growth not only at the individual but also at the macroeconomic level, have in particular education services, which form a larger share of human productive capital, and medical services, which ensure a high level of physical and moral health. Thus, an important catalyst for modern growth in the efficiency and stability of social production is medical services provided by the health care system.
Keywords: medical services